To find \(8.76 - 26.54\) using the additive inverse, you can rewrite the subtraction as an addition problem by using the additive inverse of \(26.54\).
-
Find the additive inverse of \(26.54\), which is \(-26.54\).
-
Rewrite the expression: \[ 8.76 - 26.54 = 8.76 + (-26.54) \]
-
Now, add the two numbers: \[ 8.76 + (-26.54) = 8.76 - 26.54 \]
-
Now, compute the sum:
- Start with \(8.76\).
- Subtract \(26.54\): \[ 8.76 - 26.54 = 8.76 + (-26.54) = -17.78 \]
So, the result of \(8.76 - 26.54\) is \(-17.78\).